Dealing with Religious, Cultural, and Spiritual Pluralism in Adult and Higher Education Practice in an Age of Terrorism: Challenges and Controversies - Elisabeth J. Tisdell; Derise Tolliver; Nadira Charaniya; Jane West Walsh (Adult Education Research Conference, 2002)
This symposium addresses the challenges, controversies, and perceived responsibilities in dealing with religious, cultural, and spiritual pluralism in adult education practice from the perspective of a multiple presenters of different positionalities and spiritual traditions.